87.9k views
0 votes
Solve the Equation.
6x−3(x+8)=9

x=?

2 Answers

6 votes
First distribute -3 into the parenthesis. you will get 6x-3x-24=9. Then subtract 6x and 3x because they're like terms. you will get 3x -24=9. After that add 24 by both sides and get 3x=33. this step is easy just divide by both sides and you will get x.
User Krzak
by
5.4k points
5 votes

Answer:

x = -5

Explanation:

Simplifying

6x + -3(x + -8) = 9

Reorder the terms:

6x + -3(-8 + x) = 9

6x + (-8 * -3 + x * -3) = 9

6x + (24 + -3x) = 9

Reorder the terms:

24 + 6x + -3x = 9

Combine like terms: 6x + -3x = 3x

24 + 3x = 9

Solving

24 + 3x = 9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-24' to each side of the equation.

24 + -24 + 3x = 9 + -24

Combine like terms: 24 + -24 = 0

0 + 3x = 9 + -24

3x = 9 + -24

Combine like terms: 9 + -24 = -15

3x = -15

Divide each side by '3'.

x = -5

Hope this Helps

I hope this is correct


User Ankurvsoni
by
5.9k points